PENGEMBANGAN SOAL HOTS DALAM MATERI LUAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI KELAS 4 SD KURIKULUM MERDEKA - Yulia Friska, Sonia; Syarif Sumantri, Mohamad; Gumelar Fajar Rakhman, Gumgum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce a product in the form of a book containing questions about the area of ​​flat shapes that is effective and efficient for improving critical thinking skills on HOTS questions. This type of development research is a research method used to produce certain products and test the practicality of the product. The model used is the ADDIE development model. Based on the results of trials on the development of HOTS questions, the material on the area of ​​flat shapes at SD Negeri 20 Sitiung meets the valid and practical categories. Based on the assessment results of 3 validators, the HOTS question on the area of ​​flat shapes received a percentage of 81% in the valid category. After analysis based on categories, namely: graphic content received a valid category with a score of 32 and a percentage of 80%, language received a valid category with a score of 32 and a percentage of 80% and material received a valid category with a score of 23 and a percentage of 83%.